Pengaruh Pendidikan Kesehatan Reproduksi dengan MediaPermainan Ular Tangga terhadap Pengetahuan dan Sikap Siswa SMP di Selo Boyolali - Maarif, Syamsul, Yuli Kusumawati, SKM., M.Kes (Epid) (2017)
According to BPS (2012) Selo occupied the first sequence of early marriage cases in Boyolali. The high number of early marriage cases can cause problems in adolescent reproductive health. Therefore, adolescents need an education and roductive health services in order to be able to maintain their reproductive health and not do early marriage. The purposes of the study is to analyze the effect of reproductive health education with a ladder snake game against the knowledge and attitude of junior high school students in Selo, Boyolali. This research uses Quasi Experimental with pretest-posttest with Control Group design. The population in this study were VII and VII grade ini junior high schoolas many as 377 students. The sample selection uses Proportionale Sampling, it is divided into two groups, there are experimental group and control group with 106 samples. The statistical test using Paired sample t-test showed that there is difference in the average score of knowledge (p = 0,000) and attitude (p = 0,000) in the experimental group after treatment, there is difference in the average of knowledge (p = 0,000) and there is no difference in average score of attitudes (p = 0.483) in the control group. Independent t-test results there is difference of reproduction health education effect between using game media of snake ladder and powerpoint on knowledge (p = 0,004) and at attitude (p = 0,016).